Aquacrop, crop water productivity model - Raes, Dirk (Technical Centre for Agricultural and Rural Cooperation, 2015)
Intended for agricultural researchers and stakeholders, “Aquacrop” is a crop water productivity model developed and distributed by FAO since 2009. By evaluating different parameters, it enables yields to be improved in an environment where water is scarce. A robust model that is easy to use and produces rapid results whose usefulness increases in line with the scope of challenges related to global changes.